Bioassays for the evaluation of the attractiveness of attractive targeted sugar bait (ATSB) against Anopheles mosquitoes in controlled semi-field systems - Frank S. C. Tenywa; Ummi A. Kibondo; Julian Entwistle; Osward Dogan; Mapipi Haruna; Restuta P. Phisoo; Jason Moore; Jane J. Machange; Haji Makame; Frederic Tripet; Pie Müller; Mathias Mondy; et al. (Parasites & Vectors)
Abstract Background Sugar feeding is an essential aspect of mosquito biology that may be exploited for mosquito control by adding insecticides to sugar attractants, so-called ‘attractive targeted sugar baits’ (ATSBs). To optimize their effectiveness, ATSB products need to be maximally attractive at both short and long range and induce high levels of feeding. This study aimed to assess the attractiveness and feeding success of Anopheles mosquitoes exposed to attractive sugar baits (ASBs). Method Experiments were conducted in 2 × 5 × 2-m cages constructed within the semi-field systems (SFS) at Ifakara Health Institute, Bagamoyo, Tanzania. Male and female Anopheles gambiae s.s. and An. funestus s.s. mosquitoes were exposed to either 20% sucrose or different ASB station prototypes produced by Westham Co. in either (1) no-choice experiments or (2) choice experiments. Mosquitoes were exposed overnight and assessed for intrinsic or relative olfactory attraction using fluorescent powder markers dusted over the ASB stations and 20% sucrose and for feeding using uranine incorporated within the bait station and food dye in 20% sucrose controls. Results Both male and female An. gambiae and An. funestus mosquitoes were attracted to the ASBs, with no significant difference between the sexes for each of the experiments conducted. Older mosquitoes (3–5 days) were more attracted to the ASBs (OR = 8.3, [95% CI 6.6–10.5] P < 0.001) than younger mosquitoes (0–1 day). Similarly, older mosquitoes responded more to 20% sucrose (OR = 4.6, [3.7–5.8], P < 0.001) than newly emerged Anopheles. Of the four prototypes tested, the latest iteration, ASB prototype v1.2.1, showed the highest intrinsic attraction of both Anopheles species, attracting 91.2% [95% CI 87.9–94.5%]. Relative to ATSB v1.1.1, the latest prototype, v.1.2.1, had higher attraction (OR = 1.19 [95% CI 1.07–1.33], P < 0.001) and higher feeding success (OR = 1.71 [95% CI 1.33–2.18], P < 0.001). Conclusions Data from these experiments support using ASBs v1.2.1, deployed in large-scale epidemiological trials, as it is the most attractive and shows the highest feeding success of the Westham prototypes tested. The findings indicate that future bioassays to evaluate ATSBs should use mosquitoes of both sexes, aged 3–5 days, include multiple species in the same cage or chamber, and utilize both non-choice and choice tests with a standard comparator.